Biologic tumor behavior in pilocytic astrocytomas - BOZKURT, SÜHEYLA (SPRINGER, 2012)
The aim is to describe the behavior of pilocytic astrocytoma (PAs) and its effects on patient prognosis by using flow cytometric, immunohistochemical and cytogenetic methods. We also aim to find out whether there is any difference between differently localized tumors by the above mentioned analyses. We studied DNA index, expression of p53, p16, pRb, MMAC/PTEN1, VEGF, MIB-1 index and chromosomal anomalies which can be detected by array comparative genomic hybridization (CGH) technique. We analyzed the association of the results of these studies with clinical prognosis and tumor localization. We included 53 patients (18 cerebellar, 20 chiasmatic/hypothalamic and 15 hemispheric). Samples were studied from paraffin embedded tumors. We found that PAs are mostly diploid and ploidy pattern does not affect the prognosis. The expression of p53, p16, pRb, MMAC/PTEN1 and VEGF was not significantly different between different localizations and could not predict the prognosis. Frequently seen copy number aberrations (CNAs) are: amplification in 1p36.33, 2p11.2, 9p11.2, 9q12, 16p11.2, 19q13.12-q13.2, Xp22.2-p21.3, Xp11.3-p11.22, Xq11.1-q12, Xq13.1, Xq21.1-q21.31, Xq22.3, Xq26.3 and homozygous deletion in 2p11.2, 8p23.1, 16p12.3. Among them, 2p11.2 amp, 9p11.2 amp and 1p36.21 hom del were correlated with prognosis. Moreover, we found a significant correlation between 16p11.2 amp and tumor localization. Differently localized PAs have different properties which make them behave with different biological aggressiveness. PAs demonstrate a significant amount of CNAs that can be detected by a high-resolution study. However, tumor suppressor genes p53, p16, pRb, MMAC/PTEN1 and expression patterns do not play a significant role in PAs.
Keywords: Pilocytic astrocytomas; Immunohistochemistry; Tumor suppressor proteins; Flow cytometry; Microarray; CGH; Copy number aberration; COMPARATIVE GENOMIC HYBRIDIZATION; ENDOTHELIAL GROWTH-FACTOR; RETINOBLASTOMA PROTEIN EXPRESSION; BENIGN CEREBELLAR ASTROCYTOMA; MIB-1 LABELING INDEX; BRAIN-TUMORS; PTEN GENE; GLIOBLASTOMA-MULTIFORME; CEREBRAL HEMISPHERES; DIFFUSE ASTROCYTOMAS